Effects of Greek juniper (Juniperus excelsa) extract on immune responses and disease resistance against Yersinia ruckeri in rainbow trout (Oncorhynchus mykiss) - Bilen, Soner; Ispir, Selcuk; Kenanoglu, Osman Nezih; Taştan, Yiğit; Güney, Kerim; Terzi, Ertugrul (Wiley, 2020)
AbstractThis study investigated the effects of Greek juniper extract on immune responses of rainbow trout. In this experiment, 4 doses [0 (Control), 1 (J1), 4 (J4) and 8 (J8) mg/kg] of the extract were administered orally using an oral gavage twice a day for 14 days. Immune responses were measured on 7th and 14th days. On 14th day, Yersinia ruckeri was injected intraperitoneally to all fish of all groups. On 14th day, ORP in fish of J1 group increased significantly. Lysozyme activity (LA) was increased in J8 group on 7th day (p < .05). On 14th day, a significant decrease was determined in J1 and J4 treatments in LA. Myeloperoxidase activity was significantly decreased in all groups irrespective of sampling times (p < .05). Interleukin (IL)‐1β was significantly elevated in fish of J8 group on 7th day. IL‐8 increased in fish of J8 and J4 groups on 7th day of the study. IL‐12 gene expression was significantly up‐regulated in J8 fish group on 7th day, and in J4 fish group on 14th day. Survival rate was higher in J8 treatment compared to the control and other treatments (p < .05). The results suggest that Juniperus excelsa provides protection against Y. ruckeri in rainbow trout.
Keywords: Yersinia ruckeri; Yersinia Infections; Plant Extracts; Immunity, Innate; Fish Diseases; Adjuvants, Immunologic; Juniperus; Oncorhynchus mykiss; Animals; Disease Resistance; 3. Good health